2021
DOI: 10.1523/jneurosci.2908-20.2021
|View full text |Cite|
|
Sign up to set email alerts
|

Only the Fastest Corticospinal Fibers Contribute to β Corticomuscular Coherence

Abstract: Human corticospinal transmission is commonly studied using brain stimulation. However, this approach is biased to activity in the fastest conducting axons. It is unclear whether conclusions obtained in this context are representative of volitional activity in mild-to-moderate contractions. An alternative to overcome this limitation may be to study the corticospinal transmission of endogenously generated brain activity. Here, we investigate in humans (N = 19; of either sex), the transmission speeds of cortical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 70 publications
4
17
0
Order By: Relevance
“…Moreover, the common input to the MU pool inside the β range and the resulting MU β activity were time-locked and followed cortical β rhythms by tens of milliseconds. Although determining the transmission delay by only analyzing the β power is not robust against noise that may mask the underlying shape of β bursts, our observation is in strong agreement with previous investigations using the averaged CMC ( Mima et al, 2000 ; Ibáñez et al, 2021 ). When we asked subjects to perform volitional modulations of the β activity present in the MUs via a novel neurofeedback paradigm ( Bräcklein et al, 2021 ), changes in the cortical β power were shown to be coherent with those induced in the periphery.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Moreover, the common input to the MU pool inside the β range and the resulting MU β activity were time-locked and followed cortical β rhythms by tens of milliseconds. Although determining the transmission delay by only analyzing the β power is not robust against noise that may mask the underlying shape of β bursts, our observation is in strong agreement with previous investigations using the averaged CMC ( Mima et al, 2000 ; Ibáñez et al, 2021 ). When we asked subjects to perform volitional modulations of the β activity present in the MUs via a novel neurofeedback paradigm ( Bräcklein et al, 2021 ), changes in the cortical β power were shown to be coherent with those induced in the periphery.…”
Section: Discussionsupporting
confidence: 92%
“…Neural oscillations of brain activity in the β range (13–30 Hz) are ubiquitous in the motor nervous system ( Kilavik et al, 2013 ). Alongside their pervasive appearance in the brain, β oscillations with cortical origin are transmitted linearly and at fast and stable speeds to tonically active muscles ( Witham et al, 2011 ; Ibáñez et al, 2021 ). β Activity can indeed represent an important portion of the neural inputs received by spinal motor neurons and their innervated muscle fibers, i.e., motor units (MUs; Grosse et al, 2002 ; Farina et al, 2014 ; Dideriksen et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…One possible strategy consistent with such state-dependent control of individual MUs could be relying on an input signal to MUs not directly linked to motor function and non-homogeneously distributed among the MU pool. For example, cortical oscillations could meet these criteria if descending projections of this activity to large and small MUs in a pool differed ( Ibáñez et al, 2021 ; Bräcklein et al, 2021 ; Bräcklein et al, 2022 ). A different alternative that may allow for flexible MU control after initial recruitment is volitional modulation of reciprocal inhibition ( Chen et al, 2006 ; Thompson et al, 2013 ) presumably via direct descending commands ( Jankowska, 1992 ; Nielsen et al, 1995 ).…”
Section: Discussionmentioning
confidence: 99%
“…Here, we extracted single MU activity from the TA since this muscle has properties (e.g. muscle fibres arrangement, proximity to the skin, distribution of innervation zones) that facilitate a reliable decomposition of MU activity using surface recordings ( Barsakcioglu et al, 2021 ; Bräcklein et al, 2021 ; Bräcklein et al, 2022 ; Negro et al, 2016a ; Dideriksen et al, 2018 ; Del Vecchio et al, 2020 ) and a relatively large number of monosynaptic connections with the motor cortex that could potentially be leveraged for direct independent MU control ( Ibáñez et al, 2021 ; Dideriksen et al, 2018 ). Our results strongly suggest that subjects do not tend to find or opt for a control strategy that relies on flexible MU recruitment order under constraint isometric conditions.…”
Section: Discussionmentioning
confidence: 99%
“…CMC has been explored using different neuroimaging techniques, namely MEG and EEG, but can also be computed by using EEG, sEMG and electrocorticography (Gerloff et al, 2006). Other methods such as mutual information and transfer entropy have also been explored to overcome the limitations of linear methods and to characterize non-linear correlations (Liang et al, 2020) State of the art: Currently, the study of CMC is mainly focused on how different brain areas control and modulate the activation of muscles, how the feedback from the muscles is received and processed (Sinha et al, 2020;Ibáñez et al, 2021), and how CMC can be altered due to different conditions (in particular, its modulation by fatigue (Martínez-Aguilar and Gutiérrez, 2019; dos Santos et al, 2020;Padalino et al, 2021). Current literature has established CMC as a biomarker of neurophysiology in healthy subjects (Franco-Alvarenga et al, 2019;Liu et al, 2019b) and sport conditions (Ushiyama et al, 2010).…”
Section: Cortico-muscular Coherence (Cmc)mentioning
confidence: 99%